Supervisi Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar - Evy Segarawati Ampry; Arsiah; Muh. Fathudddin Fatwa; Muh. Inayah A.M.; Arifuddin; Abdul Waqif (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The purpose of this study 1) To find out the description of the principal's supervision of the work of teachers at UPT SDN 102 Pudukku, Enrekang Regency. 2) To find out the Supporting Factors for the supervision of the principal on the work of teachers at UPT SDN 102 Pudukku, Enrekang Regency. 3) To find out the inhibiting factors for the supervision of the principal on the work of teachers at UPT SDN 102 Pudukku, Enrekang Regency. The type of research that will be used in this research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. The data analysis technique is data display, data reduction, data presentation and conclusions. The results of this study are 1) Overview of the principal's supervision of teacher work at UPT SDN 102 Pudukku, Enrekang Regency through 8 techniques that have not been implemented thoroughly but only a few techniques have been implemented, namely the technique of class visits, teacher council meetings and staff. However, classroom teaching demonstration techniques and bulletin publishing have not been carried out; 2) The supporting factors for the supervision of the principal on the work of teachers at UPT SDN 102 Pudukku, Enrekang Regency, namely the purpose of education has been understood by the teacher, and there is feedback from the supervisor; 3) The inhibiting factor for the supervision of the principal on the work of teachers at UPT SDN 102 Pudukku, Enrekang Regency is the ineffective and efficient use of time, and the absence of standards for implementing supervision by supervisors.